Skötsel av torvmarksskogar - vad vet egentligen Västerbottens skogsbolag? - Edh, Frida; Haglund, Caroline (SLU/Dept. of Forest Ecology and Management, 2012)
About a quarter of the Swedish land area is covered with shallow or thick peat. There is a potential to increase forest production in Sweden with almost 2 million m3/year in selected peatlands with low conservation values. This increase can be accomplished by drainage, complementary drainage, ditch maintenance operations and fertilization. The purpose of this study was to determine the level of knowledge regarding the management of forests on peatlands and was restricted to selected forest companies in Västerbotten County, with offices in Umeå. Three companies were chosen, SCA, Holmen and Norra Skogsägarna. Representatives from these companies were interviewed and asked to fill in a questionnaire regarding the management of peatland forests. The questionnaire was tested on beforehand in a pilot study with kind cooperation of other SLU students. The answers to the questions were recorded anonymously as Företag 1, 2 and 3 (F1, F2 and F3, subjected randomly). The number of correct answers was relatively low compared to the pilot study. F1 and F3 had 3 and F2 had 2 out of 9 correct answers, respectively. The conclusion of the study was that the knowledge among the professionals is partially deficient and that a deeper understanding is needed. In the current situation the management of peatland forests is limited due to conservation and certification. Should nature conservation and certification rules be eased and site so that the most suitable peatlands can be utilized, a deeper knowledge on peatland forestry and it’s potential would be required.